EDUCATIONAL POTENTIAL OF THE 20TH CENTURY PHILOSOPHICAL ADVENTURE FICTION - Y. Y. Kozmina (Образование и наука)
The paper explores the potential impact of studying the 20th century philosophical adventure fiction on educational process. In spite of the well-recognized idea of M. M. Bakhtin about the equality of classical and grotesque-fantastic aesthetic traditions, the former still predominates in the secondary and higher school curricula. The research aims to demonstrate the educational opportunities of the philosophical adventure fantasy; the content of the given concept being defined along with its specific features: unconditional world description, experimental plot type, discrepancy between the fantastic world created by the author and the real laws of nature, the hero’s experience in the alien world, related moral and philosophical problems.The author substantiates the idea of incorporating  the number of philosophical adventure novels into the Literature course in secondary schools, and the Theory and History of Literature course in  the higher schools of the humanities profile to facilitate the detailed and in-depth comprehension of theoretical topics concerning literary genres, types of literary heroes, grotesque adventure traditions, fantasy types, etc.